Dependency of cohesive laws of a structural adhesive in Mode-I and Mode-II loading on moisture, freeze-thaw cycling, and their synergy - Heshmati, Mohsen; Haghani, Reza; Al-Emrani, Mohammad (Materials & design, 2017)
In recent years, adhesive bonding has found its way to construction applications such as bridges. Given the harsh conditions that such structures are usually exposed to, it is necessary to account for environmental factors, particularly moisture and temperature, in the design phase. Cohesive zone modelling has attracted much attention in the last decade as a promising method to design adhesive joints. Despite this interest, the effects of moisture and thermal cycles on cohesive laws have not been investigated to the knowledge of the authors. In this paper, we present a method to directly measure the environmental-dependent cohesive laws of a structural adhesive loaded in pure Mode-I and Mode-II. Special consideration is given to overcome issues such as the time-consuming nature of moisture ingression and specimen dimensions, which could be problematic due to the size-limitations of conditioning equipment. The accuracy of this method was verified through simulation of the experiments using the finite element analysis. The effects of exposure to 95% relative humidity, immersion in saltwater and distilled water, and freeze-thaw cycles in the presence or absence of moisture were investigated. The results indicate the damaging effects of combined saltwater and freeze-thaw cycles which were clearly reflected on the shape of the cohesive laws. [Display omitted] •The open-face geometry leads to accurate estimation of cohesive-laws if a strong and thin secondary adhesive bond is used.•Saltwater reduced the peak stress of Mode-I cohesive-law which caused the largest reduction of fracture energy by 29%.•Combined freeze-thaw and saltwater led to the largest reduction of Mode-II fracture energy by 26%.•Exposure to environmental conditions were found to have different effects on Mode-I and Mode-II cohesive laws.